2012
DOI: 10.21608/eajbsz.2012.14304
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and biomass distribution of intertidal fauna in sonmiani bay (Miani Hor), balochistan (pakistan)

Abstract: A year long study of seasonal variations in community structure and biomass of sandy intertidal zone was carried out in Sonmiani Bay (Miani Hor), Balochistan. The samples were collected, by using a small beach seine and experimentally designed small beam trawl to collect the pelagic, demersal and benthic intertidal organisms. The sampling was carried out from January 2002 to December 2002 during the low tides duration. A total of 84 species were recorded mainly comprised of three major faunal groups e.g. fishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
(22 reference statements)
1
8
0
Order By: Relevance
“…This compares to other studies, such as one that found Mollusca comprised nearly 40% of the total fauna assemblage in Sonmiani Bay, Balochistan. 33 In the present observations, diversity and abundance of mollusk was common group among the macrobenthic fauna of all stations.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This compares to other studies, such as one that found Mollusca comprised nearly 40% of the total fauna assemblage in Sonmiani Bay, Balochistan. 33 In the present observations, diversity and abundance of mollusk was common group among the macrobenthic fauna of all stations.…”
Section: Discussionsupporting
confidence: 58%
“…The mollusks were the most diverse and abundant group of animals that formed 39.37% of total fauna assemblage in Sonmiani Bay, Balochistan. 26 Moreover, the diversity of marine mollusks was distributed in South East coast of India (63 species), 27 inner gulf of Thailand (18 species), 28 Malaysia (30 species) 29 and Philippine (57 species). 30 In the present observation, the most common macrobenthos were the molluscs Chthamalus depressus, followed by Saccostrea cucullata, Sepifer bilocularis, Amphibalanus reticulatus, Cerithidea cingulata, Megabalanus tintinnabulum, Thais mutabilis, Polinices didyma, Nassarius stolatus and Littorina scabra.…”
Section: Discussionmentioning
confidence: 99%
“…Dineshbabu (2011) reported the presence of Charybdis feriata throughout the trawling season (August to June) with a peak fishery commencing December and terminating June. Gondal et al (2012) reported a seasonal variation in biomass of fauna in a sandy intertidal zone in Sonmiani Bay (Miani Hor), Balochistan of Pakistan. They further reported that among crustaceans, Portunid crabs formed a total biomass of about 9.27% of which P. pelagicus accounted for 68.59% of total crab biomass.…”
Section: Discussionmentioning
confidence: 99%
“…No significant variations were recorded in seawater physical parameters according to Kane et al (2015), as most metabolic activities of aquatic organisms, particularly fishes are pH-dependent because their normal pH value is of fishes recorded Sindh and Baluchistan coast and observed associated threats of fish fauna similar finding (Santos et al, 2002;Gondal et al, 2012;Afsar et al, 2013;Chowdhury et al, 2019;Hassan et al, 2020a). The variation in biodiversity might be correlated with seasons or warm sea waters shows high species diversity index than in colder regions as reported by Ahmed et al (2013).…”
Section: Physicochemical Parameters Of Seawatermentioning
confidence: 90%